Politics and culture in international history - Bozeman, Adda B. (Princeton, 1960)
THE IMAGE of the world as a physically indivisible entity was formulated slowly in the history of mankind as the con tinents were discovered and explored. It acquired new di mensions of meaning with the steady improvement of com munications between the once isolated regions of the earth. The acceleration of contacts between the world's various peoples that fol lowed in the wake of these developments suggested a transposition of the image of wholeness, in the sense that the world could now be viewed as the abode of men whose various destinies were inextricably intertwined. This spiritual, as well as physical, version of unity re ceived further definition when it became evident that certain ideas and institutions, first tested and defined in Europe and North America, had a universal appeal. Most of the peoples outside the Atlantic community of nations accepted the standards of intellectual and material achievement that Occidental thought and enterprise represented, subscribed to the vocabulary of political symbols that had been composed in the West, adopted the forms of government that Europeans and Americans had devised, and acknowledged the validity of the tenets of international intercourse long associated with the European system of states. They thus came to see both their present and their future in terms of West ern aspirations and achievements and, since the historical records of most Asian and African peoples were first compiled and analysed by Occidental scholars, even viewed their past in the mirror of Western historiography. This widespread diffusion of the Western legacy, which was at tended by an intense propagation of the literate knowledge accumu lated in Europe and America, had the undeniable effect of providing the modern society of nations with a unifying structure. It was in strumental also in fostering the assumption that all peoples participate in a world culture and constitute a world community.
Keywords: International Relations